Simulasi Distributed Binary Power Allocation Pada Sistem Radio Kognitif - darmawan, erwan; Fernando, Iqbal (Teknik Informatika Fakultas Ilmu Komputer, 2023)
Cognitive radio is a technology for wireless communication networks that employ the upcoming Dynamic Spectrum Access ( DSA ) . DSA technology allows users who do not have a license called the secondary spectrum users to use the licensed spectrum that primary users while not in use. Application of DSA by secondary users to improve the spectrum utilization efficiency without disrupting or causing interference to the primary user. Later developed into a multi - user cognitive radio or cognitive radio networks use frequency spectrum together with a primary user ( PU ). Methods switch 'off' the user who gives the biggest interference to PU is the best method with the greatest increase in performance, both the capacity and the number of active SU while the combination of methods switch 'off' the user who raised the largest overall interference with the method switches 'off' user given biggest interference to the PU is an alternative method that shows the consistency of performance improvement in the number of potential users over 10 and able to dominate the entire method over another is begun saturation and decreased capacity. Abstracts are made in two languages, English and Bahasa Indonesia. Abstract more about background, purpose, up to, the results of research, and manai research. Abstract contains up to 250 words, single write spaces with italics (Italics) for English abstracts. Below the abstract are listed keywords consisting of six words, where the first word is again the forward. Abstract in Indonesian can be a translation of an English translation. Tiff editor for abstract syncing for reasons of abstract content